Logarithmic Sobolev inequality for a class of measures on configuration spaces - Ul Haq, A.; Daletskii, A. (Methods of Functional Analysis and Topology, 2013)
We study a class of measures on the space Γ _X of locally finiteconfigurations in X=R^d, obtained as images of ’’lattice’’ Gibbs measures on X^Z^d with respect to an embedding Z^dR^d. For these measures, we prove the integration by parts formula andlog-Sobolev inequality.